The influence of body posture parameters on selected parameters of the dynamic foot analysis - Sztandera, Paulina (Journal of Education, Health and Sport, 2018)
Introduction and purpose of work. The correct body posture and its evaluation in children of all ages is of great importance. Special attention should be paid to two critical periods, when the posture may deteriorate significantly. Monitoring the body posture makes it possible to detect any abnormalities at an early stage that may subsequently lead to other health problems. The aim of the paper was to analize the connections between the body posture parameters and the selected parameters of the dynamic foot examination. Material and methods. 106 children at the age of 10-15 years old from schools located in the Świętokrzyskie Voivodeship took part in the study. The posture of children assessed with the use of the Diers system is analyzed using a three-dimensional light-optical system. The next stage of the research was to conduct the dynamic foot analysis on the FreeMed platform. Results. No dependence between the majority of the studied body posture parameters and the parameters of the dynamic analysis was found. A statistically significant dependence was observed between: the right foot surface and the pelvic tilt, the right foot surface and the rotation surface, the number of steps per minute and the pelvic tilt, the contact time of the right foot surface and the pelvic tilt. When the pelvic tilt was standard, the authors observed a smaller surface while loading the right foot, a greater number of steps, and a shorter right foot contact time. The standard surface rotation affected the larger foot surface in the dynamic analysis. Conclusion. The study needs to be continued and extended in order to verify if there are any dependencies between the body posture parameters and the selected parameters of the dynamic analysis of the foot and gait pressure in children.